Fusion of technology management and financing management - Amazon's transformative endeavor by orchestrating techno-financing systems. (February 2020) - Tou, Yuji; Watanabe, Chihiro; Neittaanmäki, Pekka
Abstract: Amazon became the world R&D leader in 2017 by rapidly increasing R&D investment. Its R&D investment in 2017 was double that of 2015, 5 times that of 2012, and 10 times that of 2011. This rapid increase continued in 2018, and Amazon accomplished a skyrocketing increase in its market capitalization, closing to being the world's biggest company. Such a rapid increase in R&D and subsequent market value has raised questions about how to conduct R&D and secure a large amount of funds needed for high-risk investments. Amazon has provided hypothetical answers to both of these questions. Amazon has been conducting innovative R&D to transform routine or periodic alterations into significant improvements during the R&D process and claiming huge expenses for such transformation activities as expenses for R&D. The company's ample free cash flow generated by sophisticated cash conversion cycle (CCC) management endorsed a large amount of investment for such a high-risk strategy. Increased R&D induced business advancement and lean cost structure construction leading to a further increase in cash flow has stimulated interactions between vendors, customers, and Amazon via the Amazon marketplace. Activated interaction-accelerated CCC advancement, a subsequent free cash flow increase, and user-driven innovation have thus simultaneously accelerated R&D transformation. All of these components - R&D transformation and technopreneurial strategy consisting of technology management, as well as marketplace development and CCC-driven cash flow generation consisting of financing management - function together as a consolidated sophisticated machine. Thus, Amazon has succeeded in fusing technology management and financing management by orchestrating all techno-financing systems. In light of increasing concerns regarding R&D expansion without the dilemma of a productivity decline that most digital economies are now confronting, this paper demonstrates the above hypothetical answers. Following the authors' preceding analysis of Amazon's unique technology management toward a new concept of R&D in the digital economy, an intensive empirical analysis focusing on the development trajectory of Amazon's techno-financing system over the last two decades was conducted. An insightful suggestion as to neo-open innovation that fuses technology management and financing management is thus provided. Highlights: Amazon's R&D endeavor in orchestrating techno-financing systems was empirically analyzed. Sources leading Amazon a rapid and notable increase in R&D investment were identified. Sources enabling Amazon noteworthy cash conversion cycle were identified. Answer to a question of Amazon's securing large amount of R&D funds was provided. Suggestion to open innovation that fuses technology and financial management was provided.